Seed predation and removal from faeces in a dry ecosystem - Velez, Silvina (2015)
The fate of dispersed seeds from mammal faeces depends both on the animal that finds the seeds and environmental conditions. We explored the simultaneous influence of microhabitat and food availability on seed predation and removal from faeces by different animals in a protected Prosopis flexuosa open woodland site of the central Monte desert (Argentina). Using exclusion trials on simulated cattle faeces, we quantified seed predation in situ (within cages) and seed removal from faeces by rodents and ants in two different microhabitats (under shrub cover and on bare soil). This was done for two levels of availability of P. flexuosa fruits (during the fruiting season of P. flexuosa and when there are no fruits on the ground). We found that 67.9% of seedsremained in faeces, 28.9% were removed, and 3.2% were depredated in situ. Rodents removed more seeds under shrub cover than on bare soil, and during the non-fruiting period than during the fruiting period, whereas ants removed similar proportions of seeds in different microhabitats but almost exclusively during the fruiting season. This work acknowledges the complexity of dispersal processes and identifies the relative importance of some environmental factors for seed fate.